Erratum to: Evaluation Performance of Pneumatic Dryer for Cassava Starch [18 (4): 216-223] - Editorial, Reaktor (Dept. of Chemical Engineering, Diponegoro University, 2020)
Correction to: Reaktor (2018), 18 (4): 216-223 (doi: https://doi.org/10.14710/reaktor.18.04.216-223) An error appeared in the article entitled “Evaluation Performance of Pneumatic Dryer for Cassava Starch” published in Reaktor. In the published article the acknowledgement was:The authors would like to thank Widiantara, Maria Agustin Taolin and Dea Endah, Y. for supporting in preparation of materials this research. The acknowledgement of the article is corrected to be: none The original article can be access online at: https://doi.org/10.14710/reaktor.18.04.216-223 How to Cite This Article: Suherman and Hidayati, N. (2018), Evaluation Performance of Pneumatic Dryer for Cassava Starch, Reaktor, 18(4), 216-223,http://doi.org/10.14710/reaktor.18.04.216-223. Permalink/DOI: http://doi.org/10.14710/reaktor.20.03.159-159